An Alternative Model for Constitutional Question Adjudication in Indonesia: A Comparative Study of Ten Constitutional Court Jurisdictions - Dhenasya Sukma Hardaningtyas; Muchamad Ali Safa'at; Dhia Al-Uyun (International Journal of Business, Law, and Education, 2026)
Indonesia's constitutional review system entrusts the Constitutional Court with the authority to review statutes against the 1945 Constitution, yet it does not provide a procedural channel through which ordinary judges may refer constitutional doubts arising in pending cases. This doctrinal and comparative legal study formulates an alternative model of constitutional question adjudication for Indonesia by examining ten constitutional-court jurisdictions: Austria, Italy, Germany, South Africa, South Korea, Hungary, Croatia, Romania, the Czech Republic, and the Russian Federation. The study uses statutory, conceptual, case-based, and comparative approaches and analyses primary legal materials, constitutional-court legislation, judicial decisions, and relevant scholarship on centralized constitutional review and concrete norm control. The findings show that constitutional question mechanisms share several core features: they arise from concrete litigation, are normally initiated by judges, require the challenged norm to be decisive for the pending case, usually suspend the underlying proceedings, and produce decisions with binding force beyond the individual dispute. At the same time, the jurisdictions differ in their referral filters, admissibility thresholds, procedural timelines, and remedial effects. Building on these comparative findings, this article proposes a semi-mandatory judicial referral model for Indonesia. The model requires constitutional amendment to Article 24C of the 1945 Constitution, preliminary screening by the Supreme Court, strict admissibility criteria, a stay of proceedings, expedited review by the Constitutional Court, and final and binding decisions with erga omnes and limited retroactive effects. The proposed model preserves judicial independence, reduces the risk of docket congestion, and strengthens preventive protection of constitutional rights in concrete adjudication.